The Excessive Implementation of ISIC on the Obstruction in the Implementation of KBLI 2020 - Fawwaz Aiman; Nanda Mahardhika Septiansyah; Isya Fahrizky Ardianto; Endang Sutrisno; Gusti Yosi Andri (Riviera Publishing, 2024)
The Indonesian Standard Industrial Classification (KBLI) is a collection of business classification codes developed by the Central Statistics Agency (BPS) to categorize business and economic activities in Indonesia. Based on the International Standard Industrial Classification (ISIC), KBLI is integrated into the Online Single Submission (OSS) system, functioning as a tool for issuing business licenses and informing policy design. However, its implementation faces challenges, including the presence of irrelevant and non-functional codes, such as code 92000 for gambling activities, which contradict legal and social norms in Indonesia. This research aims to determine whether the adoption of KBLI over ISIC is excessive, leading to legal implications. A normative juridical approach or doctrinal research method is employed in this study, utilizing secondary data from the legal foundations of ISIC and KBLI, along with other related regulations. The results indicate that the excessive application of ISIC in KBLI has several negative impacts on its effectiveness. Codes irrelevant to the legal and social context in Indonesia render the issuance of business licenses ineffective and contradict the legal requirements stipulated in the Civil Code (KUHPerdata). The findings suggest that efforts are needed to enhance the effectiveness of KBLI in fulfilling its role as a classification system for business fields and economic activities in Indonesia. This can be achieved by considering relevance and local context to avoid unintended legal implications.